THE APPLICATION OF PROJECT BASED LEARNING MODELS IN MATERIALS OF GROWING AND CUTTING EQUIPMENT IN CLASS XI MACHINE TECHNIQUES SMK NEGERI 1 PALANGKA RAYA 2016/2017 - Lori Androvo; Debora (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2017)
This research aimed to know: (1) teacher activity while applying learning of Project Based Learning on the subject matter of the Grinding chisels and cutting tools, (2) student activity of eleventh grade students machining techniques of SMK NEGERI 1 Palangka Raya while following application of learning model of Project Based Learning, (3) students response at eleventh grade students Machining techniques of SMK NEGERI 1 Palangka Raya on learning by using the learning model of Project Based Learning (PBL) on the subject matter of the grinding chisels and cutting tools, (4) the result of student learning of eleventh grade students machining techniques of SMK NEGERI 1 Palangka Raya after following learning model of Project Based Learning (PBL)) on the subject matter of the grinding chisels and cutting tools. This research was quantitative descriptive, this research took subject of eleventh grade students machining techniques of SMK NEGERI 1 Palangka Raya selected as research subject. The instruments used were Cognitive Learning Result Test, Students Activity Sheet, Teacher Activity Sheet and Student Response Questionnaire, and student learning outcomes involving Cognitive and Psychomotor aspects. The results of data analysis indicated that the overall shows that the student activity performed well. The completeness of cognitive learning tests individually there were 27 finished (96%) and 1 unfinished (1%). Classically this learning was said to be completed because the percentage of completeness obtained (90.61%) And students' psychomotor learning achievement test (82%).